Retrospective cohort study on preparation regimens for frozen embryo transfer - Monique Atkinson; Jenny Crittenden; Howard Smith; Cecilia Sjoblom (Bioscientifica, 2021)
The objective of this study was to examine the pregnancy outcomes from frozen embryo transfer (FET) cycles using different endometrial preparation regimens, compared to ovulation induction with letrozole (letrozole OI). A retrospective cohort study was conducted at a fertility centre in Sydney, Australia, on 6060 FET cycles. The cycles were stratified into one of four ways to achieve endometrial preparation. These were either a natural, letrozole OI, OI with follicle-stimulating hormone (FSH OI) or a programmed cycle. The primary outcome was live birth rate (LBR) per embryo transfer. Secondary outcomes included clinical pregnancy and biochemical pregnancy rates, adverse events including miscarriage, ectopic pregnancy, stillbirth, neonatal death and multiple births. Ovarian stimulation parameters were also analysed including the time taken to reach the luteal phase and the number of blood or urine tests required for monitoring the cycle. The results of the study showed that the LBR following letrozole OI cycles was higher when compared to natural cycles (odds ratio (OR): 1.27 (1.07-1.49)) and programmed cycles (OR: 2.36 (1.67-3.34)). There was no significant difference between letrozole OI and FSH OI LBR (OR: 0.99 (0.76-1.28)). An improved LBR with letrozole OI compared to natural cycles was maintained when only women with a normal length cycle were considered (OR: 1.44 (1.10-1.89)). There was a significant reduction in miscarriage rates when letrozole OI was compared to programmed cycles (OR: 0.46 (0.26-0.83)). It was therefore concluded that the use of letrozole OI for endometrial preparation in an FET cycle may be associated with higher LBR and lower miscarriage rate, compared to using a programmed cycle.